The Affect Of The Asean China Free Trade Agreement (Acfta) On The SME's Performance: Pengaruh Perjanjian Perdagangan Bebas Asean China (Acfta) Terhadap Kinerja UKM - Setiyono, Wisnu Panggah; Andriyani, Dewi; Putra, Boy Isma (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2019)
This research is aimed to analyze the influence of ASEAN-China Free Trade Agreement (ACFTA) on the financial performance of SMEs in Sidoarjo. The financial performance of SMEs in this study was measured by the level of sales comparation between the period before and after ACFTA. This research applied mix method technique with squids mixed method strategy, especially sequential explanatory strategy. It is a strategy for the researchers to combine the data that was found from one method with the other method. The steps were begun with the researcher collecting the quantitative data by performing different test or Paired samples T-test then continued with collecting the qualitative data by doing library research. The results show that there are significant differences in financial performance; first, it is seen from the sales between before and after ACFTA, and second, it is proven that that the existence of ACFTA significantly affects the sales rate of SMEs.